Development of a wearable exoskeleton rehabilitation system based on hybrid control mode. (11th October 2016) - Long, Yi; Du, Zhi-jiang; Wang, Weidong; Dong, Wei
Lower limb rehabilitation exoskeletons usually help patients walk based on fixed gait trajectories. However, it is not suitable for unilateral lower limb disorders. In this article, a hybrid training mode is proposed to be applied in rehabilitation for unilateral lower limb movement disorders. The hybrid training includes two modes, that is, the passive training mode and the active assist mode. At an early stage of the rehabilitation therapy, the passive training mode is utilized, in which microelectromechanical systems-based attitude and heading reference system is used to collect the gait trajectory of the healthy limb. The exoskeleton on the unhealthy limb will be driven to track the joint trajectory of the healthy limb. If the patient's abilities recovered, the rehabilitation system can be switched to the active assist mode. Two force sensors are imbedded into the interface on the thigh to measure the interaction information in order to detect the patient's initiative walking intention. In the active mode, the walking gait trajectory is modified and generated based on the gait trajectory of the healthy side via the attitude and heading reference system. In this article, a position close control loop is designed to drive the mechanical leg to help the unhealthy limb walk. Laboratory experiments are performed on a healthy human subject to illustrate the proposed approach. Experimental results show that the proposed method can be applied and extended in the passive and active rehabilitation mode for the unilateral lower limb disorders.